Comparison between Reference Infliximab (Remicade) and its Biosimilar (Remsima) in Patients with Ankylosing Spondylitis: A Field-based Pharmacoeconomic Study - Fadhil, Hasan Raid; Al-Jumaili, Ali Azeez; Al Ani, Nizar (AL-Kindy College Medical Journal, 2023)
Background: Ankylosing spondylitis is a chronic inflammatory disease that mostly involves the spine and sacroiliac joints. It is associated with a decreased quality of life. Biological medicines such as infliximab and its biosimilar are the mainstay treatments for active ankylosing spondylitis.Objective: The study objective was to conduct a pharmacoeconomic study comparing the cost-effectiveness of the reference infliximab with its biosimilar in ankylosing spondylitis patients visiting public hospitals.Subjects and Method: This is a two-center pharmacoeconomic study performed at two large teaching governmental hospitals in Baghdad, Iraq, which supplied infliximab to outpatients with ankylosing spondylitis. The outcome data were obtained from patient’s medical records and face-to-face interviews with the patients from December 2021 through April 2022. The Independent T-Test was used to measure the differences in areas of utility, and quality of life, between the two infliximab groups.Results: The study recruited 62 patients with ankylosing spondylitis who received infliximab (31 received Remicade, and 31 received Remsima) for at least 12 weeks at two public teaching hospitals. The mean age of the patients was 37.85 years and 83.9% were men. In general, both reference infliximab and its biosimilar were successful in increasing the quality of life. Their importation costs were different from 2019 to 2021. The incremental cost-effectiveness ratio of reference infliximab versus biosimilar was $ 40,909/quality-adjusted life year (QALY) according to 2019 pricing. In contrast, in 2021 reference infliximab (Remicade) was less expensive and yielded slightly better quality of life improvement than biosimilar (Remsima) making Remicade more cost-effective (dominant).Conclusion: Remicade was slightly superior to Remsima in quality of life improvement. However, it was difficult to determine whether the reference or its biosimilar was more cost-effective in 2019 because the health officials did not specify a willingness to pay per quality-adjusted life year. Compared to Remsima, Remicade was more cost-effective in 2021 because it was less expensive and more effective in terms of quality of life improvement.